A randomized pilot study of dietary treatments for polycystic ovary syndrome in adolescents. Issue 3 (1st July 2015) - Wong, J. M. W.; Gallagher, M.; Gooding, H.; Feldman, H. A.; Gordon, C. M.; Ludwig, D. S.; Ebbeling, C. B.
Summary: Background: Evidence is lacking to recommend one diet over another when treating polycystic ovary syndrome (PCOS). Objectives: To obtain preliminary data, comparing the impact of a low‐glycaemic load (LGL) vs. low‐fat (LF) diet on biochemical hyperandrogenism in overweight and obese adolescents with PCOS. To ascertain feasibility of recruiting study participants, in partnership with an adolescent clinic, and implementing dietary interventions. Methods: Randomized controlled trial of 19 overweight and obese adolescents with PCOS and not using hormonal contraceptives (HCs). Interventions comprised nutrition education, dietary counselling and cooking workshops to foster adherence to a LGL (45% carbohydrate, 35% fat, 20% protein) or LF (55% carbohydrate, 25% fat, 20% protein) diet over 6 months. Serum bioavailable testosterone was the primary outcome. Results: Sixteen (LGL, n  = 7; LF, n  = 9) participants completed the study. Body fat percentage decreased ( P  < 0.05) in response to the interventions, with no difference between the LGL and LF groups (−1.2% vs. −2.2%; P  = 0.16). Bioavailable testosterone did not change for either group (−0.4 vs. −1.8 ng dL −1 ; P  = 0.35). Regarding feasibility, recruiting adolescents posed a challenge, and use of HCs was a main reason for ineligibility. Participants attended 5.9 of 6 in‐person visits and 2.6 of 3 cooking workshops, completed 4.9 of 6 telephone counselling calls, and reported high satisfaction with the diets and cooking workshops (≥8 on a 10‐cm scale). Conclusions: Dietary interventions were beneficial for weight control but did not attenuate biochemical hyperandrogenism. Innovative strategies are needed to recruit adolescents for studies aimed at assessing independent effects of diet on features of PCOS.